PMO-230 Clinical risk factors for Crohn's disease postoperative recurrence are reflected in alterations in mucosally adherent microbiota at surgical resection. (28th May 2012) - Murugananthan, A U; Bernardo, D O; Tozer, P; Hart, A L; Knight, S C; Whelan, K; Arebi, N; Al-Hassi, H O
Abstract : Introduction: Clinical risk factors for Crohn's disease (CD) recurrence after ileo-caecal resection (ICR) include smoking status, perforating disease and >1 surgical resection. The underlying mechanisms contributing to clinical risk are unknown. We aimed to study the relationship between risk factors and gut microbiota. Methods: Samples of macroscopically inflamed and non-inflamed small bowel from patients undergoing surgical resection for CD were analysed. Samples were snap frozen in liquid nitrogen. Cryosections were cut and the frozen sections were hybridised with oligonucleotide probes targeting the microbial 16S rRNA of total bacteria, Escherichia coli, Bacteroides-Prevotella, Faecalibacterium prausnitzii, Clostrium coccoides - Eubacterium rectale and bifidobacteria. The hybridised mucosa associated microbiota (MAM) were identified and quantified. Patients with ≥1 risk factor were classified as high risk for disease recurrence. Results: Fifteen patients underwent ICR (10 female); 9 were high risk (6 smokers, 4 fistulating disease and 2 recurrent resection- 3 patients had multiple risk factors). Faecalibacterium prausnitzii numbers in inflamed operative samples were lower in smokers compared with non-smokers (p=0.036). High-risk patients had lower numbers of bifidobacteria in both inflamed (p=0.006) and non-inflamed (p=0.01) operative samples compared with low risk patients. Conclusion: The risk of post-operative CD recurrence may be predetermined at a pre-operative stage due to dysbiosis. The role of MAM as a tool to stratify risk requires further study. Drugs that modulate MAM may, in future, play a role in reducing post-operative recurrence. Competing interests: None declared.